Act as an element of illegal aquatic extraction industry: a question of conceptual apparatus in current and potential criminal law - Dudorov O.; Kamensky D. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького, 2023)
Purpose. The purpose of the article is to compare the elements of a criminally illegal act, currently designated as illegal fishing, game or other aquatic extraction, under the current Criminal Code of Ukraine and the draft of the new Criminal Code of Ukraine. Methodology. The methodology includes a comprehensive analysis and elaboration of provisions of the current and projected (potential) criminal law of Ukraine and other countries, scientific sources, materials of law enforcement practice, as well as the formulation of author’s conclusions and recommendations. During the research, the following methods of scientific knowledge were used: comparative-legal, logical-semantic, formal-logical, systemic-structural, modeling. Results. According to the results of the conducted research: 1) it is proposed to abandon both the word construction “occupation with... water extractive industry” used in the current Criminal Code of Ukraine, and the phrase “possession of a natural resource in its natural state” used by the developers of the project of the new Criminal Code of Ukraine; 2) it has been proven that preference should be given to generalizing names of relevant articles of the draft Criminal Code of Ukraine (such as illegal extraction of natural resources from their natural state or illegal extraction of natural resources), which should be combined with the mention of specific types of illegal actions in relation to certain natural resources in the dispositions; 3) shortcomings of the articles of the project of the new Criminal Code of Ukraine, dedicated to the destruction or damage of natural resources, violations of hunting or fishing rules, acquisition or sale of known illegally extracted natural resources, have been clarified. Originality. In the process of writing the paper, the shortcomings of the project of the new Criminal Code of Ukraine were identified in terms of describing the elements of criminal offenses against the order of use of natural resources, in particular those of them that can be considered “successors” of illegal fishing, game or other aquatic extractive activities, and ways to eliminate these shortcomings were proposed. Practical significance. The results of the research can be used in law-making activities when improving the project of the new Criminal Code of Ukraine.